2005
DOI: 10.1002/ijc.21153
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A and its non-immunosuppressive derivative NIM811 induce apoptosis of malignant melanoma cells inin vitro andin vivo studies

Abstract: Advanced melanoma is a highly malignant tumor with an increasing incidence that has a poor prognosis due to resistance to common therapeutic strategies. We have demonstrated previously that cyclosporine A (CsA) induces apoptosis of rat glioma cells, reactive astrocytes, and fibroblasts. In our present study, we investigated effects of CsA and its nonimmunosuppressive derivative NIM811 on survival of human and murine melanoma cells. We demonstrated that CsA and NIM811 affect survival of human and murine melanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…For example, calcineurin inhibitors are able to increase the phosphorylation of SOX9 and thus its translocation to the nucleus (27). Interestingly, a new calcineurin inhibitor without immunomodulatory effects has shown promising results in treating melanomas (28). Deacetylase inhibitors can increase SOX9 expression not only in chondrocytes but also in sarcomas (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…For example, calcineurin inhibitors are able to increase the phosphorylation of SOX9 and thus its translocation to the nucleus (27). Interestingly, a new calcineurin inhibitor without immunomodulatory effects has shown promising results in treating melanomas (28). Deacetylase inhibitors can increase SOX9 expression not only in chondrocytes but also in sarcomas (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, CsA alone (0.1 -2 mM for 5 or 24 h depending on cell line) caused no PARP inactivation. Importantly, several in vitro studies have shown that CsA alone can induce apoptosis (PARP inactivation) although at much higher concentrations (30 -60 mM) (Pyrzynska et al, 2002;Ciechomska et al, 2005). The in vitro data on the combination of IT and CsA encouraged us to examine the effects in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…CsA is a well-known inhibitor of peptidylprolyl isomerase activity of CypA and has been studied in lung cancer, mainly in the context of chemotherapy regimens via its inhibition of the P-glycoprotein multidrug resistance protein (31)(32)(33). It has been shown to induce apoptosis in cancer cells, such as retinoblastoma and melanoma, but the exact mechanism has not been elucidated (34)(35)(36). CsA has several drawbacks as a therapeutic agent (i.e., through ''off-target'' effects-CsA is a potent immunosuppressant through inhibition of the calcineurin/nuclear factor of activated T-cell pathway in T cells, and by effects on transforming growth factor h-CsA has been shown to cause tumor progression in non-small-cell lung cancer; ref.…”
Section: Discussionmentioning
confidence: 99%